L’interprétation des contrats suivant la théorie des attentes légitimes de l’assuré - Belleau, Claude (Assurances)

(untitled) (HEC Montréal, 1992)
The author examines recent decisions in assurance Law, specifically the american rule of reasonable expectations of the insured which is applied as an aid to the interpretation of ambiguous contractual terms. This rule of intepretation has been formally applied for the first time in Quebec by the Supreme Court. The author considers that such a rule is a corollary to the principle that contractual ambiguities in a contract of adhesion are to be resolved against the insurer. ln the author's opinion, it would be necessary to clarify this rule in the Civil Code. A basic principle that governs the interpretation of a policy is that it should be construed to give effect to the mutual intend of the parties to the contract which could limit the insured's desires.